Developing A 3D Action-Adventure Game Called “Code - E” for Learning C++ Function Codes - Muhammad Kamil Zainol Abidin; Azniah Ismail (Journal of ICT in Education, 2021)
This paper describes a game prototype development project named “Code-E” for players learning and practicing their knowledge about coding while playing. Our research is based on design and development research (DDR) methodology. The main purpose of our project was actually to create a 3D action-adventure game with interesting gameplay for educational purposes that can be used by students (i.e., players) as part of their coding practice. Our chosen topic was C++ function codes. Rapid Application Development Model was used as the development method to allow us to focus on minimizing the planning stage and maximizing prototype development. First, the gameplay idea was designed. A quick prototype was developed to assist the potential users to understand the gameplay easily when we were asking for their feedback on requirements. To collect them from potential users, we used interviews. Very fortunately, our first gameplay idea was well accepted which required minimal improvement. Then, we designed and developed a full game prototype using Roblox. A questionnaire session was then conducted to get further feedback from our potential users. The 5-Likert scale questions were categorized into three categories: the game’s technical features, its gameplay concepts, and its usability as a learning tool. We used median values to interpret the Likert data. Our findings showed that the “Code-E” game prototype was well-functioned and well-accepted by our potential users. Some improvements were still required to enhance its ability in terms of difficulty level and motivation.